Patty's Toxicology 2001
DOI: 10.1002/0471435139.tox111
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Black

Abstract: Carbon black is a powdered form of elemental carbon in the form of near‐spherical colloidal particles and coalesced particle aggregates of colloidal size, obtained by partial combustion or thermal decomposition of hydrocarbons. It is distinguishable from other commercial carbons, such as charcoal, by its fine particulate nature and the shape, structure, and degree of fusion of the particles observed with the electron microscope. The fundamental unit of a carbon black particle is the aggregate. Although carbon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…This review of the Chinese cross-sectional studies identified showed elevated pro-inflammatory cytokines among workers with considerably high exposure to CB. The mean concentration of 14.9 mg/m 3 measured by personal air samples was up to 4-fold greater than the American Conference of Governmental Industrial Hygienists (ACGIH) threshold limit value (TLV) value for CB of 3 mg/m 3 (inhalable fraction) or worldwide CB OELs which generally range from 2-4 (3 mg/m 3 ) as the inhalable fraction ( 1 ).…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…This review of the Chinese cross-sectional studies identified showed elevated pro-inflammatory cytokines among workers with considerably high exposure to CB. The mean concentration of 14.9 mg/m 3 measured by personal air samples was up to 4-fold greater than the American Conference of Governmental Industrial Hygienists (ACGIH) threshold limit value (TLV) value for CB of 3 mg/m 3 (inhalable fraction) or worldwide CB OELs which generally range from 2-4 (3 mg/m 3 ) as the inhalable fraction ( 1 ).…”
Section: Discussionmentioning
confidence: 78%
“…CB particulates are usually highly agglomerated, with 10–1,000 particle aggregates per agglomerate having aerodynamic diameters of up to 200–400 nm. Based on the definition of the European Commission in 2011 that 50% of the primary particles (constituent of the aggregate) measured in the number size distribution have a diameter that is less than or greater than 100 nm, commercially available CB grades fall into one of the two categories: nanoforms of CB or non-nanoforms of CB, with the vast majority of CB grades falling into the nanoform category ( 1 ). In occupational inhalation exposure scenarios, CB particles satisfying the nano definition form agglomerates.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, greater than 95% of worldwide carbon black production is via the oil furnace black process [ 2 ]. Different grades of carbon black are typically produced by using different reactor designs and by varying the reactor temperatures and/or residence times [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, greater than 95% of worldwide carbon black production is via the oil furnace black process [Wang et al, 2004]. Different grades of carbon black are typically produced by using different reactor designs and by varying the reactor temperatures and/or residence times [McCunney et al, 2001].…”
Section: Introductionmentioning
confidence: 99%